Role and Mechanisms of Tyro3 in Podocyte Biology and Glomerular Disease - Lulin Min; Yixin Chen; Fang Zhong; Leyi Gu; Kyung Lee; John Cijiang He (Karger Publishers, 2024)
Background: Podocyte loss occurs in both primary and secondary glomerular diseases, leading to the progression of kidney disease. A large body of evidence suggests that apoptosis and detachment are the mechanisms mediating the reduction in podocyte numbers in glomerular diseases. Recent studies demonstrate a renal protective effect of protein S (PS) through the activation of Tyro3, one of the TAM receptors. Tyro3 is predominantly expressed in podocytes within the kidney, and its expression increases in early diabetic kidney disease (DKD) but decreases in patients with progressive DKD and focal segmental glomerulosclerosis (FSGS). Glomerular expression of Tyro3 also correlates with the progression of DKD and predicts the progression of primary glomerular diseases. High glucose increases Tyro3 expression, while TNF-α suppresses the expression of PS and Tyro3. PS has anti-inflammatory and antiapoptotic effects in podocytes, likely via the activation of the Akt pathway and the inhibition of NF-kB activation. In vivo, the knockout of PS or Tyro3 exacerbates podocyte loss and glomerular disease, while the overexpression of PS and Tyro3 attenuates the injury in mice with DKD and FSGS. Tyro3 agonists have also been shown to protect podocytes from injury in these animal models. Summary: Tyro3 plays a critical role in podocyte biology and glomerular disease. Tyro3 agonists could potentially be developed as a new therapy for glomerular disease. Key Message: The aim of this review article was to summarize the role and mechanisms mediating the protective effects of Tyro3 in podocyte biology and glomerular disease. Additionally, we discuss the possibility of developing Tyro3 agonists as potential treatment for glomerular diseases.